LEGAL PROTECTION FOR CUSTOMERS OF CONVENTIONAL ONLINE BANKING IN ACEH BASED ON ACEH LAW NUMBER 11 OF 2018 ON ISLAMIC FINANCIAL INSTITUTIONS - Fithia Civa Annisa (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
Qanun Number 11 of 2018 mandates that all financial transactions of the Muslim community in Aceh must be conducted through Sharia-based financial institutions. However, in reality, many people still use digital services from conventional banks such as Jenius, Bank Jago, and SeaBank. This study aims to analyse the form of legal protection for traditional online banking customers in Aceh regarding the implementation of Article 6 of Qanun Aceh Number 11 of 2018 on Islamic Financial Institutions. This research employs a qualitative method with a juridical-normative approach, utilising a literature study of relevant regulations and legal literature. The results indicate that regulatory gaps and weak supervision over access to conventional digital services persist, resulting in a disparity between legal norms and societal practices. This places users of traditional services in a legal position that the Qanun does not protect. Therefore, it is necessary to consistently strengthen the implementation of Article 6 through legal enforcement, the enhancement of digital Islamic financial literacy, and restrictions on access to conventional financial services, so that the Islamic economic system in Aceh can operate by the provisions of the applicable qanun.